Stones in water - Napoli, Donna Jo, 1948- (New York : Puffin, 1999)
After being taken by German soldiers from a local movie theater along with other Italian boys including his Jewish friend, Roberto is forced to work in Germany, escapes into the Ukrainian winter, before desperately trying to make his way back home to Venice.
4.2
5-8
Keywords: Survival -- Juvenile fiction; World War, 1939-1945 -- Juvenile fiction; Historical fiction; Survival -- Fiction; World War, 1939-1945 -- Fiction; Historical fiction; Survival -- Fiction; World War, 1939-1945 -- Fiction; Historical fiction